Analysis of Survival Strategies for Illegal Indonesian Workers in Malaysia - Silvia, Misya; Amin, Choirul (Universitas Muhammadiyah Ponorogo, 2024)
The increase in illegal Indonesian workers (TKI) every year is a polemic in itself; the opportunity to become an illegal TKI can be detrimental to the state and individual TKI because they will not get their rights and are vulnerable to problems with inappropriate labor administration. The Indonesian government must immediately resolve this problem to ensure that there are no more illegal Indonesian migrant workers coming to Malaysia. This research uses a qualitative method by collecting data through interviews, observation, and documentation from three sources on the survival of illegal migrant workers working in Malaysia. The analysis uses spatial and narrative analysis. This is a novelty in this research and direct observations in the field by the author. The research results show that the main factors for illegal migrant workers going to Malaysia are the availability of jobs, high wages, and the lure of families working there. The workers chose to be illegal because they did not have a valid visa, did not want to renew their advanced visa or a tourist visa, and switched to becoming workers in Malaysia. As for surviving as an illegal worker, the survival strategy for surviving as an illegal worker is to carry out economic, social, legal, and political survival strategies. This research is important to follow up on because many Indonesian citizens are still interested in working abroad illegally and not complying with established regulations, which can harm various parties.